2011
DOI: 10.1177/0272989x11403834
|View full text |Cite
|
Sign up to set email alerts
|

Sponsorship-Related Outcome Selection Bias in Published Economic Studies of Triptans

Abstract: The results of published economic studies of triptans are conflicting and biased. There is a tendency to select clinical outcome measures that support the sponsor's product. This leads to concern about the possible poor applicability of these results in decision making.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
11
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 40 publications
1
11
0
1
Order By: Relevance
“…These results are consistent with other studies assessing the relationship between the source of funding and the cost-effectiveness findings, specifically for oncologic drugs [2933], neuropsychiatric drugs [3436], venous thromboembolism pharmacologic prevention [37], drug-eluting stents [38], bisphosphonates for osteoporosis treatment [39], Pap tests for cervical cancer diagnosis [40]. They are also consistent with the CEAs submitted by manufacturers to health technology assessment agencies [5,6], and/or reviews selecting general cost-effectiveness studies [4,7,41,42].…”
Section: Discussionsupporting
confidence: 92%
“…These results are consistent with other studies assessing the relationship between the source of funding and the cost-effectiveness findings, specifically for oncologic drugs [2933], neuropsychiatric drugs [3436], venous thromboembolism pharmacologic prevention [37], drug-eluting stents [38], bisphosphonates for osteoporosis treatment [39], Pap tests for cervical cancer diagnosis [40]. They are also consistent with the CEAs submitted by manufacturers to health technology assessment agencies [5,6], and/or reviews selecting general cost-effectiveness studies [4,7,41,42].…”
Section: Discussionsupporting
confidence: 92%
“…[3][4][5] Industry-funded (IF) studies have been shown to report more favorable base-case cost-effectiveness values. [6][7][8][9][10][11] Mechanisms for this have been proposed, 7,[11][12][13] one of them being the tendency of IF studies to use favorable base-case values. 14,15 The association between the extent to which uncertainty is considered in a health economic evaluation and sponsorship has not been investigated.…”
mentioning
confidence: 99%
“…Examples include studies for statins in cardiovascular prevention, 58 oncologic drugs, 9,59-61 neuropsychiatric drugs, 62,63 and bisphosphonates for osteoporosis treatment. 64 The influence of industry funding on cost-effectiveness results has been considered a hot topic.…”
Section: Discussionmentioning
confidence: 99%